Controllable growth of few-layer spiral WS2. Issue 1 (21st December 2015) - Sarma, Prasad V.; Patil, Prasanna D.; Barman, Prahalad K.; Kini, Rajeev N.; Shaijumon, Manikoth M.
Abstract : Spiral and pyramidal WS2 domains controllably synthesized through chemical vapour deposition technique exhibit interesting optical properties. Abstract : Atomically thin layered transition metal dichalcogenides (TMDs) such as MoS2, WS2, MoSe2 and WSe2 have attracted great attention in recent times, due to their interesting electronic and optoelectronic properties. To realize their potential device applications, it is highly desirable to achieve controllable growth of these layered nanomaterials, with tunable structure and morphology. Here, we demonstrate chemical vapor deposition (CVD) growth of spiral and pyramid-like few-layer WS2 by controlling the growth conditions and show that these nanostructures exhibit interesting optical properties. Unique nanoarchitectural morphologies of WS2 are observed by controlling the precursors, thereby varying the initial nucleation rates in CVD growth. We discuss the growth mechanism for these spiral and pyramidal WS2 nanostructures based on a screw dislocation driven (SDD) and layer-by-layer (LBL) growth models.